2010
DOI: 10.1007/bf03262718
|View full text |Cite
|
Sign up to set email alerts
|

A two-year evaluation of four different fissure sealants

Abstract: While sealants composed of different resin matrices showed differences in retention, they were similar with respect to marginal integrity and presence of caries. Surface conditioning and the organic structure of the material are factors that may affect sealant retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Prashanth et al (27) as they concluded that the glassionomer sealant had poorer retention than the resinbased sealant. Also this result in agreement with Yýlmaz et al, (28) as they observed that the retention of "Fissurit F" was higher than compomer based sealant at 12 and 24 months follow up examination. In addition, Ninawe et al, (14) ; Oba et al (20) they reported that "Fissurit F" showed better retention than 2 flowable composite resin material used as fissure sealant.…”
Section: Laboratory Studysupporting
confidence: 91%
See 1 more Smart Citation
“…Prashanth et al (27) as they concluded that the glassionomer sealant had poorer retention than the resinbased sealant. Also this result in agreement with Yýlmaz et al, (28) as they observed that the retention of "Fissurit F" was higher than compomer based sealant at 12 and 24 months follow up examination. In addition, Ninawe et al, (14) ; Oba et al (20) they reported that "Fissurit F" showed better retention than 2 flowable composite resin material used as fissure sealant.…”
Section: Laboratory Studysupporting
confidence: 91%
“…These results in agreement with Poulsen et al (23) ; Beiruti et al (34) ; Yengopal et al (35); Niederman. (36) ; Prashanth et al (27) ; Yýlmaz et al (28) ; Seth, (37) ; Antonson, et al (33) ; Ulusu, et al (15) ; Liu et al (29) . They reported that there is no significant difference between the use of GIC and resin-based fissure sealants on permanent teeth in the prevention of dental caries.…”
Section: Laboratory Studymentioning
confidence: 99%
“…A two-year assessment of sealants based on bis-GMA resins (Fissurit F, Fissurit FX, compomer Dyract Seal and ormocer Admira Seal) demonstrated that retention of the compomer (Dyract Seal) was much lower compared to the other sealants. However, no significant differences were observed in marginal tightness of assessed sealants and in caries presence on surfaces of sealed teeth (88). In research comparing two materials -one compomer and one based on bis-GMA resin -special emphasis was placed on advantages of compomers, which are easy to use, chemically and physically durable, and they release fluorine.…”
Section: Development Of Sealing Methods and Applied Materialsmentioning
confidence: 99%
“…Recent studies showed that the level of retention of glass ionomer sealants treated by heating during setting time is considerably lower than retention of conventional composite resin for sealing. Reduced time manipulation and adhesion of glass ionomer material for the wet surface of the tooth, unequivocally favours glass ionomer material as the material of choice for sealing partially erupted molars [124][125][126][127][128][129][130]. This procedure is especially warranted in high caries risk patients, uncooperative patients and those with special needs [121].…”
Section: Retention Rates For the Fissure Sealingmentioning
confidence: 99%
“…The progression of non-cavitated occlusal lesions was slow also for surfaces that were not sealed indicating that such surfaces could either be monitored or sealed. Invasive treatment methods were not recommended [124,[126][127][128][129][130][131].…”
Section: Retention Rates For the Fissure Sealingmentioning
confidence: 99%